2002
DOI: 10.1172/jci15234
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TGF-β inhibits mammary tumor cell viability, migration, and metastases

Abstract: MethodsFc:TβRII and transgenic mice. Fc:TβRII has been described previously (11). FVB MMTV-Polyomavirus middle T antigen (MMTV-PyV mT) mice (13) (The Jackson Laboratories, Bar Harbor, Maine, USA) were housed in the Animal Care Facility at Vanderbilt University following The American Association for the Accrediation of Laboratory Animal Care guidelines. Three-week-old transgenic mice were treated twice weekly with Fc:TβRII in PBS (5 mg/kg) by intraperitoneal injection. At 110 days, tissues were harvested and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(232 citation statements)
references
References 34 publications
14
213
1
4
Order By: Relevance
“…Other groups have observed that 4T1 secretes significant amounts of TGF-␤, and that blocking TGF-␤ secretion by 4T1 enhanced the immune response primed by 4T1 (33,34). Increased IFN-␥ production by tumordraining lymph node cells was observed when mice were vaccinated with 4T1 transduced with an antisense TGF-␤ transgene (33).…”
Section: Discussionmentioning
confidence: 93%
“…Other groups have observed that 4T1 secretes significant amounts of TGF-␤, and that blocking TGF-␤ secretion by 4T1 enhanced the immune response primed by 4T1 (33,34). Increased IFN-␥ production by tumordraining lymph node cells was observed when mice were vaccinated with 4T1 transduced with an antisense TGF-␤ transgene (33).…”
Section: Discussionmentioning
confidence: 93%
“…MMTV-PymT transgenic mice develop mammary tumors with an average latency of 53 days and form lung metastases with 100% penetrance by 100 days of age (Muraoka et al, 2002). TRAMP transgenic mice develop prostate tumors with an average latency of 84 days and form lung metastases with 95% penetrance by 24 weeks of age (Gingrich et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Successful use of various types of TGF-␤ antagonists has been reported in mouse pathological models. Recombinant soluble Fc-TGF-␤ type II receptor fusion protein was used to suppress breast cancer metastasis (Muraoka et al, 2002;Yang et al, 2002). Adenoviruses carrying cDNA encoding Smad7 were used to prevent pulmonary fibrosis induced by bleomycin administration (Nakao et al, 1999), although Smad7 also blocks BMP signaling.…”
Section: Use Of C-ski (Arpg) As An Antagonist Of Tgf-␤/activinmentioning
confidence: 99%